Feasibility of a 12-Month Follow-Up in Swiss Older Adults after Post-Acute Care in Nursing Homes—A Pilot Study - Michael Gagesch; Andreas Hüni; Heike Geschwindner; Lauren A. Abderhalden; Wei Lang; Gaby Bieri-Brüning; Heike A. Bischoff-Ferrari (Geriatrics, 2023)
(1) Background: Post-acute care (PAC) aims to support functional recovery in older adults after acute hospitalization in order to regain a sufficient level of self-care facilitating their return home. However, the long-term outcomes of PAC are understudied due to challenges in recording a follow-up. We aimed to investigate the feasibility of a 12-month follow-up after PAC in Swiss nursing homes, examining practicability and potential factors influencing participation rate. (2) Methods: Collection of one-year follow-up data among 140 eligible patients after PAC in nursing homes was attempted. Patients were recruited using letters and phone calls between August and December 2017. We compared baseline data of all initial PAC patients with those who declined participation in the follow-up to identify factors potentially influencing participation. (3) Results: Overall mortality at 12 months was 25% (n = 35 of 140). Of the 105 survivors, 53 (50%) refused participation, 26 (25%) were interviewed, and 26 (25%) were lost to follow-up. Comparison of baseline characteristics between participants and objectors indicated significant statistical differences in Mini-Mental State Examination (MMSE) scores (participants mean of 26.0 [SD 3.92] vs. objectors mean of 23.5 points [SD 4.40], p = 0.015). Further, logistic regression showed statistically significantly greater odds of participation (OR 1.25 [95% CI 1.06–1.48]) for each point increase in MMSE scores. (4) Conclusions: Long-term follow-up studies in older adults after PAC are challenging due to high mortality and dropout rates. Of note, intact cognitive function at baseline was associated with a higher willingness to participate in a follow-up phone interview. The assessment of cognitive function should be considered when estimating the participation rate in older patients.